Comparison of Behavioral Concerns Priorities among Iranian Adolescent Boys, Parents and Teachers: Reporting the Results of a Modified Delphi - Fatemeh Mohammadipour; Marjan Fathi; Manzar Amirkhani; Sarah Nouriyengejeh; Ata Pourabbasi (Shiraz University of Medical Sciences, 2021)
Background: Adolescence is a time of risks and opportunities. This study aimed to investigate andprioritize the behavioral concerns of male adolescents.Methods: A modified Delphi study (2018-2019) was conducted in two stages. In the first stage,adolescents' behavioral concerns were extracted based on seven qualitative interviews and a focusgroup. Then, a questionnaire was designed using the obtained data; also, two-round consensusbuildingapproach (rating and ranking) through surveys were conducted among 90students, teachersand parents covered by the Health Departments of Tehran University of Medical Sciences, who hadbeen selected using a stratified cluster random sampling method. Qualitative content analysis was usedin the first stage and descriptive statistics in the second stage to analyze the data.Results: In the first stage, eight categories emerged, including relational challenges with parents andother adults; poor interaction with peers; lack of adaptation to conditions; emotional dysregulation;self-esteem and sense of purposefulness issues; materialistic tendencies; cyberspace issues; and nonadherenceto religious beliefs. Then 63 behavioral concerns were identified. In each round (rating/ranking), 29/27, 28/29, and 30/30, responses were received for students, parents and teachers,respectively. According to the specified scores given to different issues, ten top problems according tothe viewpoint of different groups were extracted.Conclusion: "lack of planning and prioritization skill", "insufficient skill for controlling crisis", and "lackof resilience" are the most important priority for male adolescents, teachers and parents, respectively.These findings can be used for planning programs based on the adolescents' behavioral concerns.